FEATURES OF THE PROCESS OF FORMING THE TECHNIQUE OF SPORTS MOVEMENTS WITH THE USE OF DIFFERENT TRAINING METHODS AND TAKING INTO ACCOUNT THE STRENGTH OF THE NERVOUS SYSTEM OF YOUNG ATHLETES (World Science, 2021)
Improving the efficiency of the exercise training process continues to be an important task in all sports. For several years, practical material on the use of non-traditional methods of forming the technique of sports movements in different sports in athletes with different strength of the nervous system in relation to excitation was collected and summarized. A total of 495 athletes aged 11-13 took part in the research. They were divided according to the strength of the nervous system into 3 groups: "strong", "medium" and "weak". For this purpose, the most accessible and objective methods were used: motor technique, tapping test, noise immunity test.It was found that in most cases, athletes of the strong type with greater success mastered the material in the process of problem-based learning, "weak" - when using the reproductive method, and "average" in all cases showed approximately the same results.The process of formation of technique in athletes with different strength of the nervous system proceeds differently. Regardless of the method, strong boys learn more slowly. The dynamics of change in their indicators indicates that the greatest success comes in the first lessons, when there is a mastery of the temporal characteristics of exercise. It is noticed that "strong" in the conditions of application of a game method feel more confident and show higher results, than others.